Hypoglycemic, Hypolipidemic and Histopathological Effects of Brown Seaweed (Sargassum Polycystum C. Agardh) Extracts on Type 2 Diabetic Rats - Moteshakeri, Mahsa (2011)
Diabetes mellitus is a serious global problem that is a major cause of disability and hospitalization in the world. This disorder is characterized by hyperglycemia and hyperlipidemia that are implicated in the development of microvascular and macrovascular complications. Recently, seaweeds have been the center of focus as a natural source of biological compounds useful for human health. Brown seaweed, Sargassum polycystum has been reported to be rich in biologically active substances with potential healing effects. In a preliminary study S. polycystum polar extract exhibited hypoglycemic and hypolipidemic effects on streptozotocin‐induced diabetic rats. The present study was carried out to investigate hypoglycemic and hypolipidemic effects of seaweed ethanolic and water extracts in type 2 diabetes rat model. Male Sprague‐Dawley rats (weighing 200–250 g) were divided into seven groups: normal control (NC) group fed with standard rodent diet (SRD) till the end of experiment, diabetic control (DC) group fed high‐sugar, high‐fat diet (HSHFD)for 16 weeks and then induced with 35 mg/kg body weight of streptozotocin (STZ), diabetic rats treated with 300 mg ethanolic extract/ kg body weight(DE300), diabetic rats treated with 150 mg ethanolic extract/ kg body weight (DE150), diabetic rats treated with 300 mg water extract/ kg body weight (DW300), diabetic rats treated with 150 mg water extract/ kg body weight (DW150), and diabetic rats treated with 250 mg metformin/ kg body weight (DM). Diabetes was induced in all diabetic groups by feeding rats with daily fresh prepared HSHFD for 16 weeks and then injection of low dose streptozotocin. Body weight, blood glucose level and serum lipid parameters were measured in 16 weeks. The HSHFD‐fed rats exhibited significant increase (P<0.05) in body weight (BW) over time while significant increase (P<0.05) was also observed in NC group. Low‐density lipoprotein‐cholesterol (LDL‐C)increased significantly (P<0.05) in HSHFD‐fed group as compared to NC group. High‐density lipoprotein‐cholesterol (HDL‐C) and HDL‐C/TC ratio decreased significantly (P<0.05) in HSHFD‐fed group as compared to normal control group. However, fasting blood glucose, triglyceride (TG) and total cholesterol (TC) levels did not change significantly (P>0.05) as compared to normal control group. Besides, homeostasis model assessment of insulin resistance (HOMA‐IR)showed significantly higher (P<0.05) insulin resistance index in HSHFD‐fed rats as compared to normal control group. Furthermore, after 2 hours of glucose challenge, the rats in the HSHFD‐fed group all presented higher (P<0.05) blood glucose concentration than did the NC group. The HSHFD‐fed rats presented a fasting plasma insulin that was significantly (P<0.05) higher than that of NC group in intraperitoneal glucose tolerance test (IPGTT). At the end of 22 days of seaweed treatment DC, DW300 and DE300 exhibited significantly (P<0.05) lower body weight than NC group. Fasting blood glucose levels (BGL) were significantly (P<0.05) reduced in all diabetic treated groups except in DW150 group. DW300 appeared to be more insulinotropic but it was not significant (P>0.05) compared to DC, while treatment with metformin significantly (P<0.05) increased insulin level. There was a significant reduction (P<0.05) in the percentage of HbA1c in the DE300, DE150, DW300 and DM groups compared to DC group. All seaweed extracts reduced total cholesterol and triglyceride level significantly (P<0.05) compared to DC group. LDL‐C level was significantly (P<0.05) reduced in DW300 group compared to DC group. HDL‐C/TC ratio was significantly (P<0.05) improved in DE150, DW300, DW150 and DM groups compared to DC group. Pancreas histopathological results showed significantly (P<0.05) lower lesions in all treated groups compared with DC group. Moreover, regeneration of islets of Langerhans with more intact appearance was found in DE300, DW300 and DM groups compared with DC, DE150 and DW150 groups. However, DE150, DW150 and DM groups showed fewer lesions in the liver and kidney tissues compared to DC, DE300 and DW300 groups. High doses of both extracts have more hypoglycemic properties with better regeneration effects on pancreas than low doses. However, 150 mg/kg of seaweed ethanolic and water extracts caused fewer side effects on the liver and kidney tissues as compared to the high doses (300 mg/kg). Sargassum polycystum extracts showed good hypoglycemic and hypolipidemic effects with pancreas regeneration properties,hence may be potentially useful for the prevention of metabolic syndrome. It is preferably to be used at low dosage of about 150 mg/kg body weight, since higher dosage may cause some liver or kidney lesions. Keywords: Sargassum polycystum, Brown seaweed, Type 2 diabetes, Hypoglycemic, Hypolipidemic, Sprague‐Dawley.